2001
DOI: 10.1097/00001888-200105000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Why Arenʼt There More Women Leaders in Academic Medicine? The Views of Clinical Department Chairs

Abstract: The chairs universally acknowledged the existence of barriers to the advancement of women and proposed a spectrum of approaches to address them. Individual interventions, while adapting faculty to requirements, also tend to preserve existing institutional arrangements, including those that may have adverse effects on all faculty. Departmental or school-level changes address these shortcomings and have a greater likelihood of achieving enduring impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
187
1
21

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(213 citation statements)
references
References 4 publications
4
187
1
21
Order By: Relevance
“…However, although overt barriers to women in academic medicine greatly diminished during the twentieth century, it appears that the percentage of female faculty has not changed much in the last 2 decades, despite the increasing number of women entering medical school and the increasing number of women among physicians. In most countries in Europe and in North America, the "bottle neck" for women appears to be primarily at the associate professor and full professor levels (34,(46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…However, although overt barriers to women in academic medicine greatly diminished during the twentieth century, it appears that the percentage of female faculty has not changed much in the last 2 decades, despite the increasing number of women entering medical school and the increasing number of women among physicians. In most countries in Europe and in North America, the "bottle neck" for women appears to be primarily at the associate professor and full professor levels (34,(46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, women in positions of authority found that their attempts to provide individual mentoring to others were ignored or even thwarted. For example, female chairs in medical schools found that males, as well as females, under their leadership were more resistant to reporting to them or accepting their leadership styles and decision-making [46].…”
Section: Mentorship Programsmentioning
confidence: 99%
“…Este estudio demostró que únicamen-te el 6% de los puestos de dirección estaban ocupados por mujeres. Esta evidencia ha hecho hincapié en la falta de mentores efectivos, oportunidades de desarrollo profesional y ambiente de trabajo libre de ideologías de género [28]. Este estudio fue realizado en Estados Unidos, por lo que podemos imaginar la situación en países con otro tipo de mentalidad y oportunidades.…”
Section: Liderazgo Y Mujerunclassified
“…Los autores consideran que esto es importante para el continuo desarrollo y para servir de ejemplo a las nuevas generaciones [33]. En muchas ocasiones, la causa de este retraso en la participación de la mujer en la vida académica reside en la dificultad que afrontan las mujeres para encontrar buenos tutores, oportunidades de desarrollo laboral y ambiente laboral libre de discriminación [28].…”
Section: Mujeres En Medicinaunclassified